THE INFLUENCE OF COLLABORATION BRANDING ON PURCHASING DECISIONS (Case Study On Aice Blueberry Cookies Ice Cream Products) - Kusumadewi, Intan (Jurnal Mekanika dan Manufaktur, 2025)
The rapid business competition in Indonesia results in business challenges for a company. In the current era, consumers are very careful in finding, buying, and using a product that suits what they want. Therefore, a company is required to find what kind of marketing strategy so that the products they offer can become the main choice of consumers to make purchasing decisions. This study aims to determine how co-branding influences purchasing decisions for consumers of Ice Cream Aice Blueberry Cookies. This research is included in survey research using a verification description. The population used in the study were consumers of Aice Blueberry Cookies in Majalengka with a sample size of 100 respondents. The data collection technique in this study was the distribution of questionnaires using a Likert scale. The results of this study indicate that co-branding is in the very good category, and purchasing decisions are in the high category.